Secondhand smoke exposure and autism spectrum disorder: a meta-analysis - Fadzrul Hafiz Johani,; Nur Ezdiani Mohamed,; Mohd Shafik Abd Majid,; Siti Diyana Ibrahim,; Zaleha Md Isa, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Nicotine exposure during early life can significantly affect neurocognitive development. This meta-analysis was conducted to explore whether an association exists between secondhand smoke (SHS) exposure and risk of autism spectrum disorder (ASD) in children. Database search using PubMed, SAGE, Scopus, ScienceDirect, ProQuest, and Google Scholar were used to search observational studies from January 2009 until January 2020. The random-effect model was used to combine results from individual studies. Four studies (2 cross-sectional studies, 1 case-control study, and 1 mixed design study) with 2,434 ASD cases and a total of 104,128 participants were included in the analysis. The pooled odds ratio (OR) was 1.36 (95% confidence interval (CI): 1.25-1.49) comparing SHS exposure in children with those who were not exposed. Heterogeneity was not significant across studies (Chi2 = 0.41, p = 0.94, I2 = 0%). Results from this meta-analysis indicated that SHS exposure has significant association with risk of ASD in children. Current findings should be confirmed through more studies including prospective cohort studies.